DISCONNECTION AMID INEQUALITY: AN INTERSECTIONAL APPROACH TO ETHNO-RACIAL MINORITIZED YOUNG WOMEN’S DIGITAL MEDIA (NON)USE - De Leyn, Tom; De Wolf, Ralf; Vanden Abeele , Mariek (AoIR Selected Papers of Internet Research, 2026)
Digital disconnection studies conceptualize disconnection as a deliberate strategy to balance the benefits and drawbacks of digital engagement to improve well-being. However, this field has been criticized for focusing on privileged subjects while overlooking how structural inequalities shape minoritized youths’ (dis)connection practices. Our 15-month ethnographic study addresses this gap by examining how ethno-racial minoritized young women navigate digital disconnection within intersecting gendered and racialized constraints. Overall, our findings challenge binary understandings of digital disconnection as either voluntary or enforced. First, participants strategically engage in disconnection to sustain digital connection, such as deleting social media apps before returning home to avoid parental surveillance. Second, disconnection emerges as a response to racialized and gendered online harassment, forcing participants to withdraw from digital spaces despite their desire to remain connected. Finally, smartphones simultaneously enable and constrain autonomy, as parental surveillance reinforces expectations of constant availability while affording greater mobility. By foregrounding digital disconnection as a negotiated and context-dependent practice, this study highlights the need for intersectional, context-aware approaches to digital media use and challenges dominant narratives of disconnection as an individualized response to digital overuse.